Survival outcomes of patients with cervical cancer and accompanying hydronephrosis: A systematic review of the literature - Vasilios Pergialiotis; Ioannis Bellos; Nikolaos Thomakos; Dimitrios Haidopoulos; Despina N. Perrea; Konstantinos Kontzoglou; Georgios Daskalakis; Alexandros Rodolakis (Frontiers Media S.A., 2019)
Hydronephrosis is a sign of advanced stage disease in patients with cervical cancer. Its presence is believed to negatively affect the survival of patients. To date, however, consensus in this field is still lacking. The purpose of the present systematic review is to gather the available data and to provide directions for future research in the field. We systematically searched Medline, Scopus, Clinicaltrials.gov, EMBASE, Cochrane Central Register of Controlled Trials CENTRA and Google Scholar databases from inception till June 2018. Overall, 22 studies were included in the present systematic review that evaluated outcomes from 8521 patients with cervical cancer. The findings of our systematic review support that hydronephrosis negatively affects the overall survival of cervical cancer patients. Specifically, the reported 5-year OS hazards ratio for hydronephrosis ranged between 1.34 and 3.74. Outcomes concerning the disease-free survival of these patients were, however, less discrete. None of the included studies reported whether the decreased survival of patients with hydronephrosis was attributed to complications of obstructive uropathy such as uremia and sepsis. Thus, it remains, to date, unclear whether placement of ureteral stents or percutaneous nephrostomy may actually benefit these patients. More studies are needed to evaluate the actual impact of hydronephrosis on survival rates at the various stages of cervical cancer and to help establish consensus regarding the optimal mode of management of these patients.